The Diversification of E- Services in Tourism Marketing – Case of Albania - Noti, Elton; Brunela Trebicka, PhD, (European Journal of Multidisciplinary Studies, 2016)
The hospitality industry provides twenty-four hour service all year long for the interested people, just like the Internet which is always online. This immediate information that the Internet presents to the potential customers and the opportunity to have a better viewpoint of the service they are going to buy, prepare them for the experience they are going to live. Ideas on website quality may differ, but there is also a great deal of common ground so there is a need for further research by the marketing experts. Therefore, it is very important for tourism businesses and other organizations, either from private, or from public sector, to understand the customer needs that are amenable to fulfillment in an online environment and strive to meet them. Some questions that can be raised are: What makes a destination website an effective marketing tool? How can success be measured? What is a successful website? How can quality and effectiveness be evaluated? The purpose of this paper is to address these questions using a literature review methodology, as well as a content analysis of some of the Albanian touristic websites. Seeing the growing role of websites as a customer contact point and virtual company office, tourism businesses are realizing the strategic importance of a website as a marketing tool for addressing consumers in electronic business environment.
Keywords: Tourism, Marketing, Website, ICT.